Research and Application of Local Water Quenched Wear-Resistant Steel Plough - ZHANG Zhen-xuan; RONG Shou-fan; LI Hong-bo; WANG Di; JIAO Ren-bao; LIU Li; SUN Ke-nan; WANG Jun-fa (Journal of Harbin University of Science and Technology)
In view of the poor wear resistance of high manganese steel ploughshare, in order to improve the toughness and wear resistance of ploughshare and reduce the fracture and wear of ploughshare, the influence of quenching method on the microstructure and properties of wearresistant steel was studied on the basis of changing carbon elements.The results show that with the increase of carbon content, the hardness of local water quenching/air quenching steel increases gradually, and the impact toughness decreases gradually. The carbon content is 0.344%, and the heat treatment process is “940℃ quenching×1.5h+local water cooling/air cooling+200℃×3h tempering”.The test steel has the best comprehensive performance. The hardness of the water quenching part is 49HRC, and the impact toughness ak value is 145J/cm2; the hardness of the air quenching part is 30HRC, and the impact toughness ak value is 260J/cm2. ?After the installation application test, the service life of the local water quenching/air quenching steel material plough is 2~3 times as long as that of the high manganese steel material ploughshare.